Local Government Discretion in Improving The Efficiency of Public Services - Sadat, Anwar; Lawelai, Herman; Satria, Eko; Sa’ban, L.M Azhar; Yudarsat, Andre Putra (LPPM Universitas PGRI Sumatera Barat, 2025)
Government discretion plays a crucial role in enhancing the efficiency of public service delivery, particularly in addressing complex societal needs. This study aims to explore the dimensions of governmental discretion, examining its potential to improve public service quality while identifying inherent challenges. The research employs a qualitative approach, including case studies, and identifies key factors influencing discretion, such as organizational culture, resource management, and legal frameworks. While discretion can encourage innovation and responsiveness, it also carries risks of mismanagement and reduced accountability without appropriate safeguards. The study's findings indicate that regional government discretion, although effective in improving public service efficiency, must be implemented with consideration of existing challenges, such as limited resources and managerial capacity. The novelty of this research lies in the integration of the concept of discretion with digital technology and the enhancement of public participation. It also offers concrete recommendations on how to improve the effectiveness of discretion in the context of more transparent and accountable local government practices. This research further emphasizes the importance of creating a clear legal framework that supports better management of discretion without posing the risk of abuse of power.